Klebsiella pneumoniae Spinal Epidural Abscess treated conservatively - Araújo, Filipe (2012)
Spinal infections are rare but potentially life-threatening disorders. A high level of clinical suspicion is necessary for rapid diagnosis and treatment initiation. The treatment combines both antibiotics and surgical intervention in the vast majority of cases. The authors report the case of a 84-year old female patient with a three week history of persistent lumbar back pain radiating to both thighs following a lower respiratory tract infection. She had lumbar spine tenderness but no neurological compromise. Her inflammatory markers were elevated and lumbar spine magnetic resonance imaging revealed L4-L5 spondylodiscitis with spinal epidural abscess. Blood cultures isolated Klebsiella pneumoniae and, since she was neurologically stable, conservative treatment with two-week intravenous gentamicin and eight-week intravenous ceftriaxone was initiated with positive inpatient and outpatient evolution.